Post-Traumatic Stress Disorder as a Systemic Cascade: A Psychoneuroimmunological Systematic Review - Tegar, Muhamad Afif; Algristian, Hafid; Mumpuni, Yekti (Indonesian Scientific Publication, 2025)
Post-Traumatic Stress Disorder (PTSD) has traditionally been viewed as a psychiatric condition; however, emerging evidence from psychoneuroimmunology (PNI) demonstrates that PTSD involves systemic physiological dysregulation extending across neural, endocrine, cardiovascular, gastrointestinal, and immune domains. This systematic review synthesizes recent findings from studies published between 2004 and 2025 to conceptualize PTSD as a psychoneuroimmunological cascade. Literature retrieved from PubMed, Scopus, and Web of Science was analyzed thematically to identify converging mechanisms of neuroendocrine, immune, and metabolic alterations associated with PTSD. The review reveals consistent patterns of hypothalamic pituitary adrenal (HPA) axis dysfunction, autonomic overactivation, chronic inflammation, gut–microbiota imbalance, and endocrine–immune cross-talk. These interconnected processes form self-perpetuating feedback loops that translate psychological trauma into systemic disease. PTSD should therefore be reframed as a multisystem disorder sustained by psychoneuroimmunological dysregulation rather than as a purely psychological condition. Integrative, multidisciplinary interventions—combining pharmacotherapy, mind–body therapies, and lifestyle modulation—are essential to restore systemic homeostasis and improve long-term outcomes. This reconceptualization expands theoretical understanding of PTSD, bridges psychiatry with internal medicine, and informs trauma-informed clinical and policy practices.